GROUP COUNSELING TECHNIQUES SELF TALK FOR HIGH SCHOOL STUDENTS’ LEARNING MOTIVATION - Khoiriyah, Siti; Maghfiroh, Nasruliyah Hikmatul; Ulwiyah, Imaratul; Ifatunnafs, Nisrina (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2025)
Self-talk is a conversation that leads to positive things and encourages individuals to be better, such as increasing enthusiasm. The purpose of this study is to change the concept of thinking, beliefs, behavior and emotional regulation. This research approach uses a quantitative method with a pre-experimental design research method of one group pretest-post test type. The population is 24 students of class XI of SMA IT Al-Ghozali Jember. With a sample of 5 female students. The data collection method used is the Wilcoxon Test. The results of this study indicate that there is an effectiveness of group counseling with the Self-talk Technique to increase the learning motivation of class XI students of SMA IT Al-Ghozali Jember. This method emphasizes increasing learning motivation to stimulate learning motivation in oneself. Keywords: Self-talk techniques; motivation to learn